Modalitas Bahasa Retorika Pidato Anas Urbaningrum Berhenti sebagai Ketua Umum Partai Demokrat (Analisis Semiotika M.A.K. Halliday) - Jaka Sindu (MediaKom : Jurnal Ilmiah Komunikasi, 2019)
The purpose of this study is to describe the meaning construction of social semiotics, political relations, and modalities subtitles rhetoric. This study uses Descriptive Research Methods, Social Semiotics research analysis method MAK Halliday, with the constructivist paradigm that sees social reality, as a result of construction, and the truth is a social reality is relative. Construction of meaning as verbal analysis are: speech style is dominated by Ethos style which indicates the case as a result of political engineering Susilo Bambang Yudhoyono (SBY); defense (pledoi or white book Anas); Anas personal imaging with style feel "bulliying", as is commonly done SBY. Anas superior construction using non-verbal body language, style of speech SBY duplicated. Anas way to deliver a speech, stressing emphasis on words, phrases, and sentences, with a flat facial expression. Assessment of text-context through social semiotics indicate conflict of interests and power between SBY and Anas Urbaningrum. Style language used is sarcasm (satire) and eufismisme (smoothing). Language modality dominated by modality possibility-sure-confidence. Criticism of the attitude of the language (modality) is the absence of evidence in the trial, so that this speech could be interpreted as political propaganda, maintaining a good image Anas Urbaningrum which in the future will come back to politics after serving his sentence. Keywords: rhetoric, text-context, and the modalities language.